DISIPLIN PEMIMPIN MENENTUKAN KEPEMIMPINAN YANG BAIK - Koesaeri S, Herry (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45, 2016)
Discipline theoretically is a condition that is created and formed through a process of behavior, learning, compliance, obedience, loyalty, and respect to therules and norms. Concomitant with leadership, discipline in the workplace covers aspects of morality, awareness to do something consciously, understanding theworking system based on rules and norms, exemplary leader’s personal attitude as an actualization of public service motivation. Discipline is one factor that determines the success of a leader to run an organization as expected by its members. Leader’s discipline would become a role model which is characterizedby rule obedience, teamwork, positive mental attitude, excellent physical appearance, and sound interpersonal communication skill. Discipline implementations as explained above continually would become a requirement of a leader who is intentionally serve the community, not to forget fulfill physical needs with healthy meals, appropriate suits, and effective time management so that daily activities would be fulfilled with joy and enthusiasm.